Evaluation of fish residues and shrimp head silages fermented with Lactobacillus fermentus isolated from pig - Castillo García, Wendy Elizabeth (2020)
The aim of this study was to determine the viability and nutritional characteristics of shrimp head silage and fish waste destined for pig feeding. In the conservation process, molasses and rice powder were used as a substrate and Lactobacullus fermentus, obtained from the digestive tract of the piglet, as a fermenter. Temperature, pH and percentage of acidity data were recorded, as well as organoleptic and nutritional characteristics in the first 30 days of conservation. The treatments were T1 = Shrimp head with molasses and yogurt; T2 = Shrimp head with rice powder and yogurt; T3 = Fish residue with molasses and yogurt; and T4 = Fish residue with rice powder and yogurt. T1 and T3 presented acidity and low pH, as well as low temperature during the first week, stabilizing the process on day 15. The fermentation of T2 and T4 was inadequate (not feasible). Aerobic mesophilic microorganisms, yeasts and fungi were within the acceptable limit in balanced feeds and the pathogenic bacterium Salmonella sp was absent. Crude protein content improved by 2.03% in T1 and 2.32% in T3. It is concluded that the T1 and T3 silages are adequate and stabilize from day 15, without containing pathogenic microorganisms and the protein content is according to the nutritional sources of animal origin for pig feeding.